Evaluation of myQA SRS detector for the stereotactic treatment plan verification - K. Vilchynska; O. Bezshyyko; V. Vashchyshyn; L. Golinka-Bezshyyko; R. Zelinskyi (Âderna Fìzika ta Energetika)
Modern radiotherapy techniques involve the use of high-modulated radiation fields. Intensity Modulated Radiation Therapy and Volumetric Modulated Arc Therapy require careful quality control to ensure that the planned dose distributions can be delivered by the treatment system. Quality assurance of the patient-specific treatment plan is often performed prior to treatment, when beams are delivered to the phantom and radiation doses are checked compared to the doses provided in the treatment planning system. In this study, myQA SRS measurements were compared to the EBT3 film measurements. The resolution of the film is 25 µm. The sufficiently high resolution of the stereotactic radiosurgery (SRS) detector (0.4 mm) makes it a potential alternative to film for real-time dosimetry. Irradiation was performed on a Varian TrueBeam linear accelerator. The gamma index criteria were 3 %/3 mm, the threshold dose was 10 %, and gamma index normalization was performed using the global maximum dose. The gamma index results obtained on film and on myQA SRS gave comparable results. The passing rate of film measurements based on gamma evaluation was 89.92 % and the passing rate of myQA SRS was 82.6 %. The average gamma values for the 3 %/3 mm global gamma analysis were 0.48 for the film and 0.594 for myQA SRS. In this study, film was chosen as the reference clinical detector with the highest resolution available today. myQA SRS, designed for verification of stereotactic plans, qualitatively and quantitatively identified areas of dose mismatch.